Esterification of Some Organic Acids with Isopropanol Catalysed by Cation Exchange Resin: Styrene Butadien Phenolformaldehde - Kamal, F.H.; Ebaid, A.R.; Barakat, A.M.; Aboul-Magd, A.S. (Asian Journal of Chemistry, 2010)
The esterification of various organic acids with isopropanol have been studied in presence of styrene butadiene phenol formaldehyde sulphonic group as a catalyst. The data for the rate constant are correlated to the second order bimolecular reversible reaction. For the esterification of acetic acid with isopropanol especially; the effect of molar ratio of reactants, reaction temperatures, amount of catalyst and of percent of added water on the reaction rate constant and on the percent conversion were studied, A linear relationship was obtained from the plots of log specific rate constant against molecular weight of the used carboxylic acids, amounts of catalyst, but is reciprocal of temperature. The values of ΔG*, ΔH* and ΔS* were calculated at each temperature and compared.